Verbalisations of Emotions in the Sociolect of Secondary School Students in the Light of Survey Research - Drożdż, Krzysztof (Respectus Philologicus, 2024)
The article contains the results of a survey on words within one of the lexical-semantic fields that can be distinguished among Polish secondary school students – the issue of using messages regarding effects/feelings in informal situations. The aim of the study was to isolate units of articles regarding emotions and their descriptions. Source material for the 1765 survey. Follow-up additional advanced testing descriptive section. The quantitative range is indicated as fields, and its exclusion is displayed based on the survey results. Featured include: colloquialisms (chicken face, embarrassment); profanity (whore); descriptions of the internal state and situation (I made a blunder, it was a disaster); loanwords and their innovations (lofciam, wiksa). The collected material makes it possible to present and partially discuss lexemes, nominative phrases, utterances and sentences used by students from selected secondary schools. The content presented in the article is real material obtained during several years of research.